Mary Warnock Ethics, Education and Public Policy in Post-War Britain - Graham, Philip (Open Book Publishers, 2021)
This biography illuminates the life and thought of Baroness Mary Warnock, whose active years spanned the second half of the twentieth century, a period during which opportunities for middle-class women rapidly and vastly improved. Warnock was described as 'probably the most celebrated philosopher in Britain.' She began her career as an Oxford University philosophy don and went on to become headmistress of an independent girls' school. Warnock subsequently chaired two select committees which produced reports of lasting significance, first to children with special needs, and second to childless couples. She then became Mistress of Girton College, Cambridge, and an active member of the House of Lords. Alongside these positions, Warnock wrote twenty books, ranging from the fields of philosophy to education and medical ethics. Her ideas were largely in tune with contemporary progressive thinking but late in life Warnock's extreme championing of assisted dying for older people won her enemies even among progressives. This authorised biography, written by a friend of the subject, will be of great value to the general reader with an interest in philosophy, ethics, twentieth-century cultural history, and the changing role of women from the 1950s onwards.